Technological features of foundation construction using vibro-reinforced soil-cement piles - Novytskyi, Oleksandr; Skrypka, Yevhenii (Academic journal Industrial Machine Building Civil Engineering, 2024)
The article examines the technological features of foundation construction using vibro-reinforced soil-cement piles. The technology is based on the bore-mixing method, which allows for pile formation without soil excavation, utilizing the existing soil as the main component of the soil-cement mixture. The use of vibro-reinforced soil-cement piles significantly increases the load-bearing capacity of foundations, reduces labor intensity in the construction process, and ensures the stable performance of the foundation in complex engineering and geological conditions. The article explores the specifics of the technological process of manufacturing vibro-reinforced soil-cement piles, particularly their formation, vibro-compaction, and the use of a high-frequency vibrator when embedding the reinforcement cage. It has been proven that the physical and mechanical properties of soil-cement piles, such as compressive strength, improve when deep vibrators are used in pile installation. A comparative analysis of vibro-reinforced and conventional soil-cement piles has demonstrated a significant increase in the load-bearing capacity of vibro-reinforced piles, which allows for a reduction in their number within foundation structures and leads to lower construction costs. Additionally, the article compares the soil cementation methods Jet Grouting, Pressure Grouting, and Deep Soil Mixing, which are used to improve soil bearing capacity and reduce deformations. Each of these technologies has its own characteristics that determine their effectiveness under different conditions. The advantages and disadvantages of each method are examined, including the ability to reach great depths, cost-effectiveness, and localized application.